2008
DOI: 10.1016/j.concog.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Born to adapt, but not in your dreams

Abstract: The brain adapts to changes that take place in the body. Deprivation of input results in size reduction of cortical representations, whereas an increase in input results in an increase of representational space. Amputation forms one of the most dramatic disturbances of the integrity of the body. The brain adapts in many ways to this breakdown of the afferent-efferent equilibrium. However, almost all studies focus on the sensorimotor consequences. It is not known whether adaptation takes place also at other ''l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…People with tinnitus do not perceive tinnitus in their dreams analogous to what is reported for many phantom limb perceptions [21, 25]. Dreams and wakefulness are both associated with awareness, but in one state of awareness there is no tinnitus (dreams), whereas in the other (wakefulness) there is tinnitus.…”
Section: Discussionmentioning
confidence: 70%
“…People with tinnitus do not perceive tinnitus in their dreams analogous to what is reported for many phantom limb perceptions [21, 25]. Dreams and wakefulness are both associated with awareness, but in one state of awareness there is no tinnitus (dreams), whereas in the other (wakefulness) there is tinnitus.…”
Section: Discussionmentioning
confidence: 70%
“…There are only a few studies mentioning dreamed body representation in amputees to date (for a review see [ 15 ]), and up to now, there is only one study with an epidemiological approach to investigate this issue in amputees [ 16 ]. This study found that 31% of 146 participants, who were able to remember dream content, recalled themselves as mostly or always intact (i.e., as before amputation).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high number of amputees who recalled themselves as having an intact body representation in dreams, the authors assumed the existence of an innate body model, predominantly opposing physical changes. However, the study by Mulder et al [ 16 ] excluded amputees without dream recall, and did not take dream recall frequency into account. This appears to be problematic since subjects with a low dream recall frequency have difficulties to give estimates about their dream content [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The older the patient at amputation, the longer their dream body resists updating, with some patients exclusively dreaming themselves with intact bodies more than 12 years after the amputation. This suggests that the HC's body representation is much more habit‐bound than the EN somatosensory representation, which adjusts much more quickly …”
Section: The Perceived Selfmentioning
confidence: 99%